Diagnostic utility of lung ultrasound in predicting the need for surfactant therapy in preterm neonates with respiratory distress - Singh, Pari; Patnaik, Suprabha; Verma, Arjun; Garegrat, Reema; Maheshwari, Rajesh; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2023)
Background: Lung ultrasound is an accurate and early predictor for surfactant replacement therapy in Respiratory Distress Syndrome (RDS) as compared to clinical parameters and chest X-ray. However, lung pathologies for respiratory distress at birth have overlapping symptomatology and low middle income countries have a higher incidence of congenital pneumonia, in addition to RDS, making the immediate diagnosis difficult. Thus, there is a need for assessing a cut-off for lung ultrasound score in the given setting. Objectives: Primary objective was to determine the diagnostic accuracy of Lung Ultrasound Score (LUS) in predicting the need for surfactant therapy in preterm neonates with respiratory distress. Secondary objectives were to correlate LUS with corresponding oxygen saturation to fraction of inspired oxygen ratio (SpO2/FiO2), arterial/Alveolar oxygen pressure ratio (a/A) and Chest X-Ray (CXR) findings. Methodology: Prospective observational study carried out at a tertiary level neonatal intensive care unit in India in 2022 enrolling 100 neonates <34 weeks gestational age with respiratory distress at birth. After initial stabilization of the neonate, LUS was performed and baseline parameters were noted. Surfactant was administered as per 2019 European Consensus guidelines and LUS was repeated after 6 hours of therapy. Results: The mean gestation of enrolled neonates was 31.06 ± 2.12 weeks and the mean birthweight was 1412 ± 391 g. Around 58% were diagnosed with RDS and 30% had congenital pneumonia. Surfactant was administered to 40% neonates. The cutoff LUS for surfactant therapy was 7 (area under curve [AUC] 0.977; 95% CI, 0.947-1; P < 0.001; with sensitivity 92.5%, specificity 96.67%, PPV 94.87%, NPV 95.08%) and the cutoff LUS for second dose of surfactant was 10 (AUC 0.964; 95% CI, 0.913-1; P < 0.001. The score decreased by 3.24 (2.44 -4.05) after 6 hours of first dose and correlated significantly with SpO2/FiO2 ratio (-0.750), a/A ratio (-0.650) and CXR findings (0.801).The study predicted an optimal LUS cutoff of 7 and 10 for the need of first dose of surfactant and re-treatment, respectively, in neonates <34 weeks gestational age with respiratory distress.